Batrachochytrium salamandrivorans elicits acute stress response in spotted salamanders but not infection or mortality. (28th January 2020) - Barnhart, K.; Bletz, M. C.; LaBumbard, B.; Tokash‐Peters, A.; Gabor, C. R.; Woodhams, D. C.
Abstract: The emerging fungal pathogen Batrachochytrium salamandrivorans ( Bsal ) is a major threat to amphibian species worldwide with potential to infect many species if it invades salamander biodiversity hotspots in the Americas. Bsal can cause the disease chytridiomycosis, and it is important to assess the risk of Bsal ‐induced chytridiomycosis to species in North America. We evaluated the susceptibility to Bsal of the common and widespread spotted salamander, Ambystoma maculatum, across life‐history stages and monitored the effect of Bsal exposure on growth rate and response of the stress hormone, corticosterone. We conclude that spotted salamanders appear resistant to Bsal because they showed no indication of disease or infection, and experienced minor effects on growth upon exposure. While we focused on a single population for this study, results were consistent across conditions of exposure including high or repeated doses of Bsal, life‐stage at exposure, environmental conditions including two temperatures and two substrates, and promoting pathogen infectivity by conditioning Bsal cultures with thyroid hormone. Exposure to high levels of Bsal elicited an acute but not chronic increase in corticosterone in spotted salamanders, and reduced growth. We hypothesize that the early acute increase in corticosterone facilitated mounting an immune response to the pathogen, perhaps through immunoredistribution to the skin, but further study is needed to determine immune responses to Bsal . These results will contribute to development of appropriate Bsal management plans to conserve species at risk of emerging disease. Abstract : The emerging fungal pathogen, Batrachochytrium salamandrivorans ( Bsal ), is a major threat to amphibian species worldwide, with the potential to invade biodiversity hotspots in the Americas. We evaluated the susceptibility of the common and widespread spotted salamander, Ambystoma maculatum, to Bsal across life‐history stages and environmental conditions and monitored the effect of Bsal exposure on growth rate and response of the stress hormone, corticosterone. While corticosterone increases initially upon exposure to Bsal, we found no indication of disease or persisting infection, and minor effects on growth upon exposure.